After COVID-19: Building a more coherent and effective workforce development system in the US - Harry J. Holzer (Institute of Labor Economics (IZA), 2021)
Workforce development in the US today is spread across higher education institutions (primarily public 2-year and for-profit colleges), labor market institutions and workplaces, with public funding from a range of sources. But outcomes for students and workers are weaker than they could be, especially among disadvantaged students and displaced workers; funding for workforce programs is insufficient and not always effective. I propose the following changes: 1) Reforms and additional funding in the Higher Education Act for postsecondary occupational training for disadvantaged students; 2) Modest taxes on worker displacement along with new funding for retraining; and 3) A permanent version of the Trade Adjustment Assistance Community College and Career Training (TAACCCT) grants, to fund partnerships between community colleges, workforce institutions and states. Together, these actions would improve credential attainment and employment outcomes among the disadvantaged and those at risk of being displaced.
Keywords: J0; I22; I23; 330; workforce development; community college; training; displaced workers